Isotretinoin does not contribute to increased neuropsychiatric risk in the overall acne population, but risk management during treatment remains essential. (1st July 2022) - Ravencroft, Jane; Eichenfield, Lawrence
Abstract: Linked Article:  Paljarvi et al. Br J Dermatol 2022; 187:64–72 .